INTER-CULTURAL FEATURES OF SELF-EXPRESSION OF STUDENTS IN COMMUNICATION - A R Akimova; M I Volk (RUDN Journal of Psychology and Pedagogics, 2015)
Modern political and cultural situation in Russia calls for a new generation of young people. In this regard we need to develop in them the personal qualities and characteristics which will enable them to achieve their personal and professional success in various spheres of life. The article is devoted to the study of inter-cultural communication features in Russian, Kazakh and Armenian students. The differences in the motives of the self-expression in students depending on the situation and communication partners, their cultural-value orientations, communicative tolerance and the manifestations of sociability, aggressiveness, proneness to conflict are revealed. The obtained results of the study gave us the opportunity to develop the practical recommendations that can significantly optimize the psychological support of students, designed to maintain and strengthen their physical and mental well-being, helping to solve problems in personal sphere and interpersonal interaction